Madrasah Culture Based Transformational Leadership Model - Nur Khoiri (FITK UIN Walisongo, 2016)
Leadership is the ability to influence, direct behaviour, and have a particular expertise in the field of the group who want to achieve the goals. Dynamic organization requires transformational leadership model. A school principal as a leader at school aims to actualizing good learning leadership. Leadership learning focuses on learning which components include curriculum, teaching and learning process, assessment, teacher assessment and development, good service in learning, and developing a learning community in schools based on organizational culture as value, assumption, belief evolved from the roots of member thought of the organization and believed by all members of the organization and implemented in everyday life that could give meaningKeywords: leadership, transformational leadership, headmaster, instructional leadership, organizational culture.AbstrakKepemimpinan merupakan kemampuan mempengaruhi, mengarahkan tingkah laku dan memiliki keahlian khusus di bidang yang diinginkan kelompoknya untuk mencapai tujuan. Oganisasi yang dinamis memerlukan model kepemimpinan transformational. Kepala sekolah sebagai pimpinan memiliki tujuan untuk mewujudkan kepemimpinan pembelajaran yang baik. Kepemimpinan pembelajaran memfokuskan pada pembelajaran yang komponen-komponennya meliputi kurikulum, proses belajar mengajar, assesment (penilaian hasil belajar), penilaian serta pengembangan guru, layanan prima dalam pembelajaran, dan pembangunan komunitas belajar di sekolah berbasis budaya organisasi yang berupa nilai, asumsi, kepercayaan yang berkembang dari akar pemikiran anggota organisasi dan diyakini oleh semua anggota organisasi serta dilaksanakan dalam kehidupan sehari-hari .